Nosocomial Rabies Encephalitis: Lessons Learned From Exposures in a Large Healthcare System. (October 2020) - Dascomb, Kristin; Singson, Karen; Frame, Cherie; Petersen, Sharon; Pande, Isabel; Peterson, Dallin
Abstract : Background: In October 2018 a patient presented to hospital A's emergency department (ED) for a work injury, arm spasms, and inability to drink liquids. He developed rapid neurologic decline and was transferred to hospital B for neurocritical care. He developed a fever, was intubated, and had an unrevealing infectious diseases (ID) consultation. He became comatose, had refractory seizures, and was transferred to hospital C. A second ID consultation revealed that he had many bats in his home, and his symptoms were consistent with rabies encephalitis. Antemortem specimens of serum, CSF, skin biopsy, and saliva were all positive for rabies virus PCR, and/or rabies serologies. Objective: We describe the response of a multihospital system to the exposure of employees across 3 facilities to rabies-infected body fluids. Methods: Three hospitals in 1 system (222 caregivers) cared for the index patient (hospital A, n = 8; hospital B, n = 107; hospital C, n = 107; 19 students and residents), as did 2 additional facilities outside the system. These included physicians (n = 21), registered nurses (n = 57), respiratory therapists (n = 29), imaging technicians (n = 24), phlebotomists (n = 12), laboratorians (n = 8) and others (n = 71). Infection prevention, employee health, and pharmacy leadership created a centralized team to ensure that all exposed caregivers were screened, and if exposed, were vaccinated. An electronic screening tool developed and administered by the Utah Department of Health via Research Electronic Data Capture (Redcap), rapidly assessed caregiver body fluid exposure risks (saliva, tears, neurologic tissue), and use of personal protective equipment in patient care. After completion, caregivers received notification that he or she (1) had no exposure (no further action), (2) had exposure and should report to employee health for vaccination, or (3) had unclear exposure and should contact the employee health department. Results: Caregivers feared that the tool underestimated exposure risk. Many caregivers (n = 48), repeated the assessment more than once, changing answers. The most common reasons cited were incomplete forms (n = 21), caregiver did not recall using personal protective equipment with contact with saliva (n = 8) or did not understand rabies transmission (n = 3). All vaccinations were initiated by 11 of 26 care givers, 18 days after initial deployment of the tool. All exposed caregivers completed the course. No caregivers developed symptoms of rabies encephalitis. Conclusions: An online tool can safely assess large healthcare exposure such as rabies. A team comprising infection preventionists, employee health representatives, pharmacists, and public health department representatives made the assessment of many geographically dispersed caregivers rapid and effective. Caregivers should employ the basic tenets of standard precautions in the daily care of patients to avoid unknown exposures to common bodily fluids. Funding: None Disclosures: None